2022
DOI: 10.1155/2022/8517728
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Cardiac Recovery after Acute Myocarditis from West Nile Virus Infection: A Review of the Current Literature

Abstract: West Nile Virus (WNV) myocarditis is nearly fatal, according to the current medical literature. We report a previously healthy 37-year-old Caucasian male who presented to our facility with two days of progressive lower extremity weakness, fever, edema, and shortness of breath found to have left ventricular global hypokinesis with an ejection fraction of less than 25%, consistent with acute viral myocarditis. He also has concomitant WNV meningoencephalitis due to his altered mentation. He was found to have a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…While initial human cases connecting WNV to myocarditis or cardiomyopathy were sparse, the surge in WNV infections has highlighted its ability to cause myocardial damage in humans as well. WNV infection has been associated with serious cardiac conditions, including fatal arrhythmias, myocardial dysfunction, elevated cardiac enzymes, ventricular tachycardia, ventricular fibrillation, and heart block [ 88 ]. In support of this, one study revealed evidence of myocardial damage in patients with WNV infection, characterized by elevated myocardial enzyme levels and electrocardiogram ST segment changes, indicating cardiac dysfunction.…”
Section: Flaviviridae Viruses and Cardiovascular Diseasementioning
confidence: 99%
“…While initial human cases connecting WNV to myocarditis or cardiomyopathy were sparse, the surge in WNV infections has highlighted its ability to cause myocardial damage in humans as well. WNV infection has been associated with serious cardiac conditions, including fatal arrhythmias, myocardial dysfunction, elevated cardiac enzymes, ventricular tachycardia, ventricular fibrillation, and heart block [ 88 ]. In support of this, one study revealed evidence of myocardial damage in patients with WNV infection, characterized by elevated myocardial enzyme levels and electrocardiogram ST segment changes, indicating cardiac dysfunction.…”
Section: Flaviviridae Viruses and Cardiovascular Diseasementioning
confidence: 99%
“…Other RNA viruses, excluding enteroviruses, found globally and associated with myocarditis include influenza A and B viruses, measles and rubella viruses, respiratory syncytial virus, parainfluenza virus, hepatitis C and E viruses, and human immunodeficiency virus [141,[178][179][180][181][182][183][184][185][186][187]. Finally, vector-borne infections caused by chikungunya, dengue, Zika, and West Nile viruses, have been associated with myocarditis [188][189][190][191][192][193][194][195][196]. These cases are rare, but should not be neglected, considering that 3.5 billion people live in areas where these viruses are endemic.…”
Section: Other Cardiotropic Virusesmentioning
confidence: 99%